Palaeobiological implications of the bone histology of Pterodaustro guinazui - Chinsamy, Anusuya (2009)
This study provides a comprehensive investigation of the bone microstructure of multiple bones of the Early Cretaceous filter-feeder, Pterodaustro guinazui, from the Largacito Formation of Central Argentina. We provide information regarding the bone histology of multiple elements from single skeletons, as well as a variety of bones from different individuals. In addition, we analysed changes in bone microstructure through ontogeny in growth series of several long bones of the taxon. Our investigation of skeletal and ontogenetic variation in Pterodaustro gives insights into the developmental growth dynamics of this unusual ctenochasmatid pterodactyloid from early ontogeny through to adulthood and also provides information pertaining to histological variability within and between bones of individuals. This study also documents the presence of what appears to be medullary bone tissue within the medullary cavity of a large femur of Pterodaustro. This suggests that, like birds, reproductively active female pterosaurs may have deposited a special bone tissue (medullary bone) to cope with the demand of calcium during eggshelling. Our study supports the hypothesis that small Jurassic pterodactyloids took several years to reach adult body size. More specifically, we provide data that suggests that Pterodaustro attained sexual maturity at about 2 years of age, and continued to grow for a further 3–4 years doubling in size before attaining skeletal maturity.